Creativity in the primary classroom - Desailly, Juliet; Sage eBooks (London : SAGE, 2012)
A textbook on how to teach creatively in primary education, and how to inspire creativity in the classroom, for those training to teach in primary education, and for practicing teachers wishing to further develop their creative approaches to teaching.
Includes index.
Specialized.
Description based on print version record.
Keywords: Creative teaching; Elementary school teaching; Electronic books